Histopathological profile of women who had previously failed in-vitro fertilization and the association to the outcome in the subsequent in-vitro fertilization cycle - Naama Steiner; Rola F Turki; Waleed El-Khayat; Ghada Al Malki; Samer Tannus; Michael H. Dahan (Korean Society of Obstetrics and Gynecology, 2022)
Objective To evaluate the endometrial histopathological profile of patients undergoing curettage and the association of the histopathological profile with the pregnancy outcome during the subsequent in-vitro fertilization (IVF) cycle. Methods In this retrospective cohort study, a total of 248 women with at least one failed attempt of IVF and who underwent curettage and a subsequent IVF were included. Demographic data, endometrial histopathological records, stimulation information, and pregnancy outcomes were collected and analyzed. Results The histopathological analysis of endometrial tissues showed that 130 women (52.4%) had endometrial pathologies. Of these women, 103 (41.5%) had endometrial polyps, 22 (8.9%) had chronic endometritis, and five (2.0%) had both polyps and endometritis. No statistical difference was observed between the normal histopathology group and the abnormal histopathology group in the outcome of the subsequent IVF cycle. Subgroup analyses were performed to further characterize and compare women with normal histopathology and women with endometrial polyps (polyp subgroup) or chronic endometritis (endometritis subgroup). No statistical differences were found among the three groups in the rates of pregnancy (44.1% vs. 49.5% vs. 45.5%, P=0.72), biochemical pregnancy loss (13.5% vs. 15.7% vs. 20.0%, P=0.86), clinical pregnancy loss (25.0% vs. 31.4% vs. 30.0%, P=0.77), and live birth (27.1% vs. 26.2% vs. 22.7%, P=0.91) during the subsequent IVF cycle. Conclusion Women with previously failed IVF and abnormal endometrial histopathology treated with curettage had the same outcome in the subsequent IVF cycle as women with normal endometrial histopathology.